Technology Shocks as the Source of Economy Fluctuations and Their Simulations Using Real Business-Cycle Model (Research Bulletins of the Faculty of Economic Sciences, 2018)
Innovation is one of the key factors of long-term economic growth. In the article the development of economic thought related to the analysis of the effects of technology-related supply shocks is presented. In particular Real Business-Cycle (RBC) model is being discussed. In the model exogenous fluctuations constitute the main factor of cyclical changes. The author discusses the applicability of the RBC model to simulate the impact of supply shocks on aggregated indicators. The article also includes a discussion of business cycles and their possible sources in the context of different economic schools. As the result it serves as a basis for the analysis of possible impact of Industry 4.0 implementation on the economy.
Keywords: technology; economy; shock; cycle; development